2022
DOI: 10.3390/ani12111378
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tannic Acid Supplementation on Growth Performance, Oocyst Shedding, and Gut Health of in Broilers Infected with Eimeria Maxima

Abstract: The purpose of this study was to evaluate effects of tannic acid (TA) on growth performance, fecal moisture content, oocyst shedding, gut permeability, lesion score, intestinal morphology, apparent ileal digestibility, and the antioxidant and immune system of broilers infected with Eimeria maxima. A total of 420 one-day-old broilers were distributed to five treatments with seven replicates of 12 birds. The five treatments were the (1) sham-challenged control (SCC; birds fed a control diet and administrated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 54 publications
3
17
0
Order By: Relevance
“…Examining coccidia oocyst shedding is an effective method to determine the level of coccidia infection [21]. The addition of tannic acid reduced the number of coccidia oocysts shed compared to that in the PC group, which is consistent with the results of previous reports [18,22,23]. The reduction in the number of oocysts in the feces indicated an increase in coccidia resistance in broilers.…”
Section: Effects Of Tannic Acid On the Fecal Coccidia Oocyst Excretio...supporting
confidence: 89%
“…Examining coccidia oocyst shedding is an effective method to determine the level of coccidia infection [21]. The addition of tannic acid reduced the number of coccidia oocysts shed compared to that in the PC group, which is consistent with the results of previous reports [18,22,23]. The reduction in the number of oocysts in the feces indicated an increase in coccidia resistance in broilers.…”
Section: Effects Of Tannic Acid On the Fecal Coccidia Oocyst Excretio...supporting
confidence: 89%
“…In addition, we aimed to assess the potential interaction effects between dietary treatments and challenge on these parameters. The results of the current study reaffirmed the reported adverse effects of Eimeria challenge on intestinal integrity, morphology, and tight junction protein gene expression ( Hong et al, 2006 ; Castro et al, 2020b ; Yadav et al, 2020 ; Choi et al, 2022 ; Teng et al, 2023 ), as well as its effects on immune responses and SCFA profiles ( Shanmugasundaram et al, 2013 ; Walston et al, 2016 ; Lin and Olukosi, 2021 ). More importantly, our findings suggested that Arg or BCAA supplementation in reduced-protein diets may have beneficial effects on intestinal integrity and immune functions of Eimeria challenged broiler chickens fed reduced-protein diets.…”
Section: Discussionsupporting
confidence: 81%
“…Our current study showed that 1 to 2 g/kg supplemental TA exhibited beneficial effects in reducing ST NR colonization in the ceca and stimulating immune system, which potentially resulted in improved growth performance in broilers infected with ST NR . Our previous study showed that 0.5 to 2.75 g/kg supplemental TA had potential to be an anticoccidial agent in broilers infected with Eimeria maxima ( Choi et al, 2022a ). However, supplemental TA higher than 1 g/kg exhibited antinutritional effects on broilers under nonchallenge conditions ( Choi et al, 2022b ).…”
Section: Discussionmentioning
confidence: 99%